Artificial Intelligence - Trivedi, Nripesh (International Journal of Scientific Research and Management (IJSRM), 2023)
Artificial Intelligence is the way one can solve problems occurring in everyday life. A lot of mathematical solutions are presented as to how one learns and the way one should learn to give rise to some kind of intelligence. Deep learning is an example of this [1]. Problems occur everywhere from mathematics to computer science. Intelligence is needed to solve problems. This paper is about that. It presents a simple method or way to solve problems intelligently. The next heading describes as to how one could solve problems in an intelligent manner.